Radiological presentation of a case of Type-III ileal atresia with unused microcolon in a rural setup- A case report - Sankalp Yadav; Gautam Rawal; Nishant Gupta (International Journal of Medical Research and Review, 2015)
Ileal atresia is the result of an in-utero vascular accident, leading to distal small bowel obstruction. Contrast enema is the primary imaging study to diagnose distal bowel obstruction. We present a case of a four day old child (neonate) with a history of bilious vomiting; diagnosed as ileal atresia with unused microcolon on plain film of the abdomen and contrast enema. In operation, the child had Type-III atresia.